2014
DOI: 10.1037/a0034418
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theory of distinct types of “impulsive” behaviors: A meta-analysis of self-report and behavioral measures.

Abstract: Impulsivity is considered a personality trait affecting behavior in many life domains, from recreational activities to important decision making. When extreme, it is associated with mental health problems, such as substance use disorders, as well as with interpersonal and social difficulties, including juvenile delinquency and criminality. Yet, trait impulsivity may not be a unitary construct. We review commonly used self-report measures of personality trait impulsivity and related constructs (e.g., sensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
673
3
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(735 citation statements)
references
References 372 publications
(284 reference statements)
48
673
3
11
Order By: Relevance
“…Relatedly, we encourage future research to examine the developmental asymmetry model using behavioral measures of these constructs as well. Although support for direct overlap between laboratory-based behavioral measures and self-reported trait measures is modest, both methods of measuring these constructs have independently predicted externalizing behavior outcomes (Cyders & Coskunpinar, 2011;Sharma et al, 2014). Thus, examining interactions between reward sensitivity and impulse control measured using laboratory tasks may provide additional support for the developmental asymmetry model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, we encourage future research to examine the developmental asymmetry model using behavioral measures of these constructs as well. Although support for direct overlap between laboratory-based behavioral measures and self-reported trait measures is modest, both methods of measuring these constructs have independently predicted externalizing behavior outcomes (Cyders & Coskunpinar, 2011;Sharma et al, 2014). Thus, examining interactions between reward sensitivity and impulse control measured using laboratory tasks may provide additional support for the developmental asymmetry model.…”
Section: Discussionmentioning
confidence: 99%
“…Impulse control has frequently been operationalized as the ability to think before acting and plan ahead (Whiteside & Lynam, 2001Wills, Ainette, Stoolmiller, Gibbons, & Shinar, 2008), and is commonly referred to as planning, premeditation, or "good self-control," with similar or identical items used as indicators of these parallel constructs (King, Patock-Peckham, Dager, Thimm, & Gates, 2014;Sharma, Markon, & Clark, 2014). A wide body of personality literature suggests a direct and inverse relation between impulse control and problem behaviors.…”
Section: Impulse Control As a Moderatormentioning
confidence: 99%
“…It would be interesting for future research to explore associations between impulsivity, self-affirmation and music performance utilising other conceptualisations of impulsivity (e.g., Sharma et al, 2014;Knezevic-Budisin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Whiteside and Lynam (2001) identified four distinct facets of impulsivity: urgency, lack of premeditation, lack of perseverance, and sensation-seeking, while Sharma, Markon and Clark (2014) suggested that impulsivity was underpinned by three distinct personality traits (e.g., neuroticism, disinhibition, and extraversion), and put forward four types of impulsive behaviour: inattention, inhibition, impulsive decision-making, and shifting. KnezevicBudisin, Pedden, White, Miller, and Hoaken (2015), on the other hand, propose a twofactor model, with one factor reflecting the tendency to act without thinking or planning and the other reflecting a need for reward, excitement and risk-taking.…”
Section: Impulsivity and Music Performancementioning
confidence: 99%
“…Para medirla como rasgo mediante autoinforme se ha propuesto el "Trait Emotional Intelligence Questionnaire" (TEIQue) 9 . La utilización de autoinformes para medición de rasgos de personalidad los ha mostrado estables 21,22 , no obstante, su uso se recomienda acompañado de tareas en laboratorio 23 , y reportes de terceros 24 , al mostrar validez incremental al evaluar personalidad y desempeño 25 .…”
Section: Inteligencia Emocional Como Rasgo De Personalidad: Concepcióunclassified